Brief communication on psychosocial work environment and wellbeing in relation to job demands-resources: A study on Malaysian public health perspective - Javaid, M.U. (Universiti Putra Malaysia, 2017)
Psychosocial risks and work-related stress are global problems and there is a limited research over such problems in developing countries. This study investigates these risks in Malaysian public health perspective by using biomarkers in relation to the workers' health and well-being. Biomarkers can be used to objectively measure the physiological response to psychosocial stressors. This study will be helpful to address the complex contemporary issues that emerge because of continuous change in the work environment. Non-proportional stratified random sampling technique was used for data collection and analysis would be done with the help of AMOS 21.0 in Structural Equation Modelling (SEM) to achieve range of outcomes. © Universiti Putra Malaysia Press.